The assault on world poverty : problems of rural development, education and health (J. Hopkins Univ. P. BaltimoreUS, 1975)
Analyzes the nature and causes of poverty. Examines ways of alleviating the problem through action in five related fielads. Outlines specific programmes for bringing the benefits of development to the poorest of the poor by increasing their productivity.
Keywords: RURAL DEVELOPMENT